2011
DOI: 10.1124/jpet.111.188136
|View full text |Cite|
|
Sign up to set email alerts
|

Development of Angiotensin IV Analogs as Hepatocyte Growth Factor/Met Modifiers

Abstract: The 6-AH family [D-Nle-X-Ile-NH-(CH 2 ) 5 -CONH 2 ; where X ϭ various amino acids] of angiotensin IV (Ang IV) analogs binds directly to hepatocyte growth factor (HGF) and inhibit HGF's ability to form functional dimers. The metabolically stabilized 6-AH family member, D-Nle-Tyr-Ile-NH-(CH 2 ) 5 -CONH 2, had a t 1/2 in blood of 80 min compared with the parent compound norleual [Nle-Tyr-Leu-⌿-(CH 2 -NH 2 )3-4 -His-Pro-Phe], which had a t 1/2 in blood of Ͻ5 min. 6-AH family members were found to act as mimics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…There has been dispute in the field as to the target that mediates the memory-enhancing effects of Ang IV, because this hexapeptide has the ability to bind to other proteins (Vanderheyden, 2009;Kawas et al, 2012;Benoist et al, 2014;. Nevertheless, the hypothesis that Ang IV and its analogs improve cognitive function through IRAP inhibition by altering levels of neuropeptides in the brain and/or exerting their actions by facilitating glucose uptake in neurons have attracted the most attention (Vauquelin et al, 2002;Albiston et al, 2003;Chai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been dispute in the field as to the target that mediates the memory-enhancing effects of Ang IV, because this hexapeptide has the ability to bind to other proteins (Vanderheyden, 2009;Kawas et al, 2012;Benoist et al, 2014;. Nevertheless, the hypothesis that Ang IV and its analogs improve cognitive function through IRAP inhibition by altering levels of neuropeptides in the brain and/or exerting their actions by facilitating glucose uptake in neurons have attracted the most attention (Vauquelin et al, 2002;Albiston et al, 2003;Chai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There is a need for improved cognitive enhancers for the treatment of Alzheimer's disease and related disorders and it is therefore not surprising that considerable efforts have been devoted to the discovery of compounds that can mimic the positive effects of Ang IV (Wolfe, 2002;Chai et al, 2008;Gard, 2008;Wright et al, 2008Hallberg, 2009;Kawas et al, 2012;McCoy et al, 2013). Both potent and specific drug-like IRAP inhibitors (Borhade et al, 2014;Mountford et al, 2014), some with proven effects in vivo (Albiston et al, , 2011, and inhibitors with more peptidic character (Kobori et al, , 1998Wolfe, 2002;Axen et al, 2006;Axen et al, 2007;Andersson et al, 2008;Lukaszuk et al, 2008Lukaszuk et al, , 2009Hallberg, 2009) have been disclosed by us and others.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our laboratory have demonstrated that various AngIV analogs, which act as "AT 4 receptor antagonists" possess structural homology with the dimerization domain of HGF. These analogs bind HGF with high affinity while blocking HGF dimerization and ultimately its capacity to activate c-Met (Kawas et al, 2011(Kawas et al, , 2012. Furthermore, there appears to be direct correlation between biological activity and the ability to inhibit HGF dimerization (Kawas et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Initial hints of a possible target are apparent in several studies that examined the mechanism of action of "AT 4 receptor antagonists" (Yamamoto et al, 2010;Kawas et al, 2011Kawas et al, , 2012, which were originally defined as AngIV-like molecules that interfered with cognition (Wright et al, 1999). These studies demonstrated that the antagonists had structural homology with the dimerization domain of the pleiotropic growth factor hepatocyte growth factor (HGF), bound to HGF with high affinity, blocked HGF's activation and subsequent activation of its receptor c-Met, and displayed both anticancer and antiangiogenic activity as would be expected of an HGF/c-Met antagonist (Peters and Adjei, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…34,37 On the other hand, AngIV has the possibility to bind and activate the hepatocyte growth factor receptor named c-Met. 38 The rate of delivery or formation, as well as elimination, are other important determinants for activity that in turn are dependent on the actual expression pattern of the RAS-associated enzymes. AngIV has been reported to be short-lived and completely degraded within five minutes.…”
Section: Discussionmentioning
confidence: 99%